Individual recognition based on human iris using fractal dimension approach - Lee, , PS; Ewe, , HT (2004)
In this paper, we present an approach for individual recognition system based on human iris using the estimation of fractal dimension in feature extraction. In this research, 500 iris images have been collected from different races for system validation. The attempt of capturing iris images in 320x240 resolution is intended to enable iris recognition in small-embedded system or portable devices with tight memory constraint and limited storage space. Hough transform and maximum vote find method are employed to localise the iris portion from the iris image. For feature extraction, a new approach based on fractal dimension is used to measure the important biometric information carried by human iris. A modified exclusive OR operator is designed to determine the failure of a match of two iris patterns. The experimental results show that the proposed method could be used to recognise an individual effectively.